44‐3: High‐Performance Color MIP LCD with New Electrode Structure. Issue 1 (28th June 2022) - Sato, Takashi; Sasaki, Takahiro; Hakoi, Hiroyuki; Kanashima, Atsuko; Maeda, Seiji; Shimada, Shinji; Minoura, Kiyoshi
Abstract : We have developed a new transflective Memory‐In‐Pixel(MIP) LCD providing good optical property and low frequency drive. To obtain high image qualities in both transmissive and reflective modes, the cell design for the transflective LCD with new electrode structure was examined. We adopted it into a prototype and successfully fabricated a 64 color MIP LCD.